2011
DOI: 10.3758/s13423-011-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

I said, you said: The production effect gets personal

Abstract: Saying a word out loud makes it more memorable than simply reading it silently. This robust finding has been labeled the production effect and has been attributed to the enhanced distinctiveness of produced relative to unproduced items (MacLeod et al. Journal of Experimental Psychology: Learning, Memory, and Cognition, 36, 671-685, 2010). Produced items have the additional information that they were spoken aloud encoded in their representations, and this information is useful during retrieval in certifying pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 22 publications
8
62
0
Order By: Relevance
“…The picture superiority effect refers to the observation that items presented as pictures are typically remembered better than items presented as (written) words. The production effect refers to the finding that words that are read out loud or are quietly (but overtly) mouthed are remembered better than words that are read covertly to oneself (Conway & Gathercole, 1987;Gathercole & Conway, 1988;MacLeod et al, 2010), or are read out loud by someone else (MacLeod, 2011). Both the production and picture-superiority effect can be explained according to the item's distinctiveness during the study phase.…”
Section: Discussionmentioning
confidence: 99%
“…The picture superiority effect refers to the observation that items presented as pictures are typically remembered better than items presented as (written) words. The production effect refers to the finding that words that are read out loud or are quietly (but overtly) mouthed are remembered better than words that are read covertly to oneself (Conway & Gathercole, 1987;Gathercole & Conway, 1988;MacLeod et al, 2010), or are read out loud by someone else (MacLeod, 2011). Both the production and picture-superiority effect can be explained according to the item's distinctiveness during the study phase.…”
Section: Discussionmentioning
confidence: 99%
“…MacLeod et al showed that people better recognized written words that they had spoken aloud or silently mouthed, as compared with words that they had silently read; the authors called this phenomenon the "production effect" . Other studies suggested that the auditory component of vocalization also enhances memory; words were better remembered when they were heard versus when they were silently read at learning (Gathercole & Conway, 1988;MacLeod, 2011). However, spoken words were better remembered than words that were either heard without being produced or silently mouthed (Gathercole & Conway, 1988), suggesting that both auditory and motor experience contribute to later memory of written words.…”
mentioning
confidence: 98%
“…The production effect is the finding that people have better explicit memory for words that they read aloud relative to words that they read silently (Hourihan & MacLeod, 2008;MacLeod, 2011;MacLeod, Gopie, Hourihan, Neary & Ozubko, 2010;. Although the benefit of vocalization for long-term memory had received periodic research attention (Conway & Gathercole, 1987;Dodson & Schacter, 2001;Gathercole & Conway, 1988;Gregg & Gardiner, 1991;Hopkins & Edwards, 1972;Kurtz & Hovland, 1953;MacDonald & MacLeod, 1998;Rosenbaum, 1962), MacLeod and colleagues have recently brought this phenomenon to the fore.…”
mentioning
confidence: 99%
“…In explaining the production effect, MacLeod and colleagues (2010;MacLeod, 2011;Ozubko, Gopie & MacLeod, 2012; have posited a distinctiveness account (inspired by the relational-distinctiveness account of Conway & Gathercole, 1987). Relative to silent reading, reading a word aloud involves the encoding of an additional dimension that stands out as distinctspeech.…”
mentioning
confidence: 99%